2023
DOI: 10.1007/s10754-023-09343-2
|View full text |Cite
|
Sign up to set email alerts
|

Children, vaccines, and financial incentives

Abstract: Recent studies have been analyzing and measuring the efficacy of the use of financial incentives to increase the Covid-19 vaccine uptake. To the best of our knowledge, this paper is the only study available in the literature that aims to measure the effect of financial incentives on vaccine rates among children. This paper explores the effects of a specific financial incentive on parents’ vaccination decisions for their children. Using data from a regional practice, where students aged 12 and older received $5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Incentives should be added, and the societal value of vaccination should be emphasised when people choose not to vaccinate because they believe the dangers exceed the benefits (Betsch et al, 2015). A study by Erdem, Erdem, and Monson (2023) found that offering a small financial incentive significantly increased the proportion of parents who vaccinated their children by 2.64 to 4.23 percentage. However, incentives may not be effective in all contexts, and there are concerns that they may lead to unintended consequences, such as reducing intrinsic motivation to vaccinate.…”
Section: Incentivesmentioning
confidence: 99%
“…Incentives should be added, and the societal value of vaccination should be emphasised when people choose not to vaccinate because they believe the dangers exceed the benefits (Betsch et al, 2015). A study by Erdem, Erdem, and Monson (2023) found that offering a small financial incentive significantly increased the proportion of parents who vaccinated their children by 2.64 to 4.23 percentage. However, incentives may not be effective in all contexts, and there are concerns that they may lead to unintended consequences, such as reducing intrinsic motivation to vaccinate.…”
Section: Incentivesmentioning
confidence: 99%